CHILD SAFEGUARDING POLICY IN LEMBAGA PENYELENGGARA KESEJAHTERAAN SOSIAL (LPKS) - Hartono, Bambang Tri (Devote: Jurnal Pengabdian Masyarakat Global, 2024)
Lembaga Penyelenggaraan Kesejahteraan Sosial (LPKS) is an institution that organizes social rehabilitation programs for children in conflict with the law. LPKS applies a social work and child rights approach to achieve children's social functioning, growth, and development in a safe environment while participating in social rehabilitation programs. LPKS chose the Child Safeguarding Policy (CSP) to uphold a safe environment. CSP is a system or collection of activities, procedures, documents, and responses in addressing child protection issues in the context of the institution. It covers a range of activities from prevention to response to child abuse issues. This article aims to describe the process of the Social Welfare Institution in implementing the Child Protection Policy. This article is a qualitative article based on the framework of constructivism and interpretivism, using ethnographic methods. Its selection is based on the benefits of collecting information through involvement in implementation, participatory observation, field notes, and report documents. The process of LPKS in implementing the Child Protection Policy implies (1) the role of leaders in demonstrating the commitment of the institution to protecting children from the risk of abuse, (2) the Child Protection Policy must be carried out integrally through awareness, prevention, reporting, and response to child abuse issues, (3) the Protection Policy must be carried out in an integrated manner.